Bergson and history transforming the modern regime of historicity - Schure, Leon ter, 1980- (SUNY series in contemporary French thought., 2019)
"In this book, Leon ter Schure demonstrates the value of Bergson's philosophy of life for a more expansive understanding of history. Bergson is known for his explorations of time as duration, yet in his writings rarely referred to history. At the same time, historians and philosophers of history have not significantly incorporated Bergson's ideas about the nature of time into their work. Modernity has brought change at an ever-accelerating rate, and one of the results of this has been a tendency toward presentism. Only the here and now matters, as past and future have been absorbed by the "omnipresent present" of the digital age. Rather than isolating human history from the history of the natural world, Bergsonism situates history within the broader framework of the evolution of life and allows us to imagine the past instead as a living resource for the invention of the future. This not only reveals a unique sense of history's creative potential, it also allows for a rethinking of important topics in the study of history, such as historical time, the survival of the past, and historical progress"--